An approach based on Stochastic Petri Nets for dependability evaluation of profibus-DP networks - portugal, pj (2004)
The paper presents a framework to evaluate dependability of PROFIBUS-DP networks. An hierarchical modeling approach is proposed, which considers both the effects of permanent and transient faults. Stochastic Petri Nets are used as the modelling technique to obtain dependability models with emphasis in the use of analytical/numerical methods to provide model's solutions. In scenarios where its difficult to apply this approach, compact simulation models are derived.